ENGLISH AS A FOREIGN LANGUAGE (EFL) TEACHERS’ PERCEPTIONS ON DIFFERENTIATED INSTRUCTION AT SMPN 49 MAKASSAR - Mirwan, Husnul Khatimah; Korompot, Chairil Anwar; Fauzan, Muh. Miftah (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study investigates the perceptions and practices of English as a Foreign Language (EFL) teachers regarding differentiated instruction at SMPN 49 Makassar. Using a qualitative descriptive methodology, data were collected through interviews, classroom observations, and document analysis. The findings reveal varying levels of understanding and implementation among teachers, highlighting the challenges and benefits of differentiated instruction. While some teachers demonstrate advanced strategies tailored to student needs, others adopt a more generalized approach. The study underscores the necessity of comprehensive teacher training and institutional support to maximize the potential of differentiated instruction within the Merdeka Curriculum framework.